Effects of Moisture Content and Heat Treatment on the Viscoelasticity and Gelation of Polyacrylonitrile/Dimethylsulfoxide Solutions - Jae-Yeon Yang; Yun-Su Kuk; Byoung-Suhk Kim; Min-Kang Seo (Gels)
Polyacrylonitrile (PAN) gels create significant obstacles in industrial fiber spinning by forming insoluble networks that compromise solution stability and uniformity. This study investigates the rheological properties of PAN/dimethyl sulfoxide (DMSO) solutions, examining how aging time, moisture content, and polymer concentration affect gelation behavior. Dynamic rheological analysis revealed that both physical and chemical crosslinks play crucial roles in gel formation, with gelation accelerating markedly when moisture content exceeds 3% and aging progresses. Under heat treatment at 80 °C, samples with increased moisture content demonstrated rapid transitions to solid-like states, indicating a critical moisture threshold for enhanced gelation kinetics. Additionally, reductions in polymer concentration disrupted physical crosslink density, thereby mitigating gel formation. These results underscore the importance of precisely controlling moisture and concentration parameters in PAN solutions to stabilize solution properties and minimize gel formation, thus enhancing process efficiency and quality in PAN-based carbon fiber production.